Pengaruh Model Pembelajaran Jigsaw Berbasis Budaya Lokal terhadap Motivasi Belajar IPAS Siswa - Agustin, Salsabila; Suprapmanto, Joko (Paedagogie, 2026)
This study intended to assess the influence of the JIGSAW learning model based on indigenous culture on students' motivation to study IPAS in Sukabumi Regency's SDN Babakan Cibatu. The low level of motivation among students, as shown by their minimal involvement in classroom activities and the continued application of traditional teaching methods that have not incorporated local culture as a learning tool, served as the impetus for the research. In turn, the learning process often becomes less contextual and less effective in assisting students in linking what they learn to their everyday lives. A quasi-experimental approach was used in this quantitative study, which had a Nonequivalent Control Group Design. Fifth-grade pupils from SDN Bojongkawung (control group) and SDN Babakan Cibatu (experimental group) were chosen via purposive sampling for the sample. A validated and reliable learning motivation questionnaire was utilized to gather data. Descriptive statistics, a normality test, and the Mann-Whitney U test were used to analyze the data. The findings showed an increase in the mean score of students' learning motivation in the experimental group, from 59.63 to 72.94, with a Sig. (2-tailed) value of 0.000 (< 0.05). These findings suggest that the IPAS learning model developed by JIGSAW based on local culture has a beneficial and significant impact on pupils' willingness to learn.